Reversal Effect of ALK Inhibitor NVP-TAE684 on ABCG2-Overexpressing Cancer Cells - Wang, Jingqiu; Wang, Jing-Quan; Cai, Chao-Yun; Cui, Qingbin; Yang, Yuqi; Wu, Zhuo-Xun; Dong, Xingduo; Zeng, Leli; Zhao, Linguo; Yang, Dong-Hua; Chen, Zhe-Sheng (Frontiers in Oncology, 2020)
Multidrug resistance (MDR) is the main reason of failure of cancer chemotherapy. Overcoming MDR mediated by overexpression of ATP binding cassette (ABC) transporters in cancer cells remains a big challenge. In this study, we explore whether NVP-TAE684, a novel ALK inhibitor which has the potential to inhibit the function of ABC transport, could reverse ABC transporter-mediated MDR. We performed MTT assay to determine cell viability and reversal effects of NVP-TAE684 in parental and drug resistant cells. Drug accumulation and efflux assay was carried out to evaluate the impact of NVP-TAE684 on accumulation and efflux of chemotherapeutic drugs. ABCG2-mediated ATP hydrolysis in the presence or absence of NVP-TAE684 was conducted to determine the effect of NVP-TAE684 on the ATPase activity of ABCG2 transporter. Western blot analysis and immunofluorescence assay were used to investigate protein molecules related to MDR. Additionally, the molecular interaction between NVP-TAE684 and ABCG2 transporter was identified by a docking simulation. MTT assay showed that NVP-TAE684 significantly reversed ABCG2-mediated MDR but not ABCC1-mediated MDR. Drug accumulation and efflux studies indicated that the reversal effect of NVP-TAE684 was related to the inhibition of efflux activity of ABCG2 transporter. However, NVP-TAE684 did not alter the protein level or change the subcellular localization of ABCG2 transporter. Furthermore, ATPase analysis indicated that NVP-TAE684 stimulated ATPase activity of ABCG2 transporter in a concentration-dependent manner. Docking analysis showed that NVP-TAE684 interacts with the substrate binding sites of the ABCG2 transporter. Taken together, our study indicates that combination of NVP-TAE684 with antineoplastic drugs could attenuate ABCG2-mediated drug-resistance, which provides a new strategy for MDR cancer treatment,